2006
DOI: 10.2459/01.jcm.0000199777.85343.ec
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dilatation in patients with bicuspid aortic valve

Abstract: The association of a bicuspid aortic valve (BAV) with abnormalities of the proximal thoracic aorta, including dilatation, aneurysm and dissection, has been previously described, leading to the hypothesis of a common underlying developmental defect involving the aortic valve and the aortic wall. Consequently, any patient with BAV should receive a careful assessment not only of the valve function, but also of the aortic root and the ascending aorta. Dilatation of the proximal thoracic aorta is a common finding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 85 publications
3
51
0
Order By: Relevance
“…The frequency of pathologic dilatation (in 25% of all patients with BAV) was similar to reported estimates from necropsy and surgical series, where it ranged from 10% to 35% [25]. It was also concordant with the prevalence of pathologic dilatation of ascending aorta reported by other authors in performed echocardiographic studies [4,8].…”
Section: Discussionsupporting
confidence: 79%
“…The frequency of pathologic dilatation (in 25% of all patients with BAV) was similar to reported estimates from necropsy and surgical series, where it ranged from 10% to 35% [25]. It was also concordant with the prevalence of pathologic dilatation of ascending aorta reported by other authors in performed echocardiographic studies [4,8].…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, CAE occurred with and without dilatation of the ascending aorta, another frequent appearance of BAV disease. 15,19,20 By retrospective review of coronary angiograms, CAE was found more than twice as frequently in CMR-confirmed BAV disease compared with TAV disease, and notably, the common coincidence of CAE and BAV disease could be independently confirmed in our in-hospital BAV registry. In this validation study, the sample size of subjects with BAV was more than twice the size of subjects with BAV disease in the initial CMR exploration study.…”
Section: Discussionmentioning
confidence: 91%
“…Most often, root dilatation is observed in younger men with BAV and is independent of the presence or severity of an aortic valve stenosis. 15,20 The aorta in BAV and Marfan syndrome patients and ectatic coronary arteries may share common histopathologic findings, including increased matrix metalloproteinase activity. 16 Moreover, the aortic valve, the proximal part of the coronary arteries, the ascending aorta, and the pulmonary trunk share a common embryonic origin, each developing from the neural crest.…”
mentioning
confidence: 99%
“…Aortic dilation (mainly involving the ascending aorta) is one of the most common non-valvular findings in BAV occurring in 35-80% of adult patients 3,4,19,37,38 . It is mainly asymptomatic and often precedes aortic dissection or rupture.…”
Section: Clinical Features Associated With Bavmentioning
confidence: 99%
“…BAV is a multifaceted, heterogeneous disorder ( Figure 1). Its natural history is determined by hemodynamic valvular impairment (present at birth or, more commonly, acquired by aging), and/ or by increased prevalence of aortic abnormalities ranging from reduced aortic elasticity to aortic dilatation/aneurysm/ dissection [1][2][3][4][5][6][7][8][9][10] . Each of the above features can be found in patients with isolated BAV or, in association with multiple congenital heart diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%